Effectiveness of Learning Management System of Universitas Negeri Malang in Supporting Distance Learning - Adi, Eka Pramono; Praherdhiono, Henry; Hatun, Dyah Infita; Prihatmoko, Yulias; Pradana, Dian Arief (JTP - Jurnal Teknologi Pendidikan, 2024)
The COVID-19 pandemic requires distance learning to be carried out by all educational institutions. The learning management system plays a crucial role in supporting modern distance learning that is carried out online. However, the effectiveness of LMS in supporting distance learning at the State University of Malang has not been known. This study aims to measure the effectiveness of LMS SIPEJAR as a learning management system owned by the State University of Malang in supporting students' distance learning. The sample of this study was students of the Department of Educational Technology batch 2019. The approach used was descriptive qualitative, with the interview method used to collect data from selected participants using a purposive sampling technique. The results showed that LMS SIPEJAR is effective in supporting online distance learning for students at the State University of Malang, although several aspects must be improved. This research can be used as a reference and recommend State University of Malang and other institutions to improve the quality of their distance learning.